Pemikiran Pendidikan Islam oleh KH. Abdurrahman Wahid (Gus Dur) - Muarifah, Muarifah; Sholekah, Umma Rahmah; Khoir, Mulyanto Abdullah (Lembaga Yasin AlSys, 2025)
This study aims to examine the concept of Islamic education from the perspective of Abdurrahman Wahid (Gus Dur), a prominent figure in Indonesian history known for his progressive and humanistic thought, particularly in the field of Islamic education. A qualitative approach was employed using a library research method, with data sourced from books and articles written by or about Gus Dur. Data analysis was conducted using content analysis to explore the meaning and substance of his educational ideas. The findings reveal that Gus Dur viewed Islamic education as a process not only for instilling Islamic values such as justice, equality, and humanity, but also as a means of fostering critical, participatory, and empathetic social consciousness. He emphasized the importance of an inclusive, tolerant, and humanistic approach to Islamic education while rejecting exclusive and discriminatory models. According to Gus Dur, education should promote respect for diversity and uphold human rights. The study concludes that Gus Dur’s educational thought remains relevant and applicable in addressing the complex and multicultural challenges of modern Islamic education. His contributions offer valuable guidance for developing a more open, democratic, and community-oriented Islamic educational system.